Cognitive behaviour therapy for anxiety in adolescent with early prodromal of psychosis at boarding school - Niken Yuniar Sari; Budi Anna Keliat; Herni Susanti (BMC, 2019)
Abstract Background Early prodromal of psychosis starts in adolescent indicated by non specific symptoms which may result in the changes of behaviour, role, function, and social interaction. Cognitive behaviour therapy is a strategic intervention in reducing anxiety symptom. The purpose of this research is to find out the effects of cognitive behaviour therapy for anxiety in adolescent with early prodromal of psychosis. Method The design of this research was Quasi experimental design: pre-post test with control group. Samples were selected after the screening on adolescents in boarding school with the Prodromal Questionnaire (PQ16). Subjects were 78 respondents consisting of 39 each groups, obtained by random sampling technique. Nursing intervention was provided to intervention group 1, while cognitive behaviour therapy was provided to intervention group 2. The measurement of anxiety in adolescents is by using the Hamilton Anxiety Rating Scale for Anxiety (HARS). The analysis was performed by Repeated Anova and Independent t-test. Result The result of the research shows that anxiety level decrease significantly on those two groups, whilst the decrease of anxiety and early prodromal of psychosis in the intervention group 2 indicates more decrease than intervention group 1. Conclusion Cognitive behaviour therapy is recommended to reduce anxiety in adolescent with early prodromal of psychosis.